Assessing the Impacts of Participatory Communication in Promoting Girl-Child Education in the Federal Capital Territory (FCT), Abuja - Ekas, Esosa Asielue (The Gender Truth Journal, 2025)
This study examines the impact of participatory communication in promoting girl-child education in the Federal Capital Territory (FCT), Abuja, Nigeria. The research is conducted in two phases, integrating both qualitative and quantitative approaches to provide a comprehensive understanding of how participatory communication strategies influence access, retention, and academic success among girls in FCT. The first phase focuses on gathering qualitative insights through focus group discussions (FGDs) and in-depth interviews with educators, parents, policymakers, and students, capturing lived experiences and perceptions on communicationdriven educational advocacy. The second phase employs a quantitative survey to assess the statistical significance of participatory communication initiatives on girl-child education, analysing variables such as enrollment rates, classroom participation, and community involvement. Findings indicate that community-driven dialogue, interactive media programmes, and inclusive decision-making significantly enhance awareness and reduce socio-cultural barriers that hinder female education. The study concludes that participatory communication serves as a crucial tool in fostering educational inclusivity, recommending policy frameworks that integrate grassroots communication strategies to enhance girl-child education in FCT Abuja. These findings contribute to existing literature by emphasising the role of communication in addressing educational disparities and advocating for sustainable interventions to bridge the gender gap in education.